PROSES PEMILIHAN PRESIDEN INDONESIA DALAM PERSPEKTIF POLITIK AL–MAWARDI> - Mohammad Alfuniam (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
Indonesia as dominantly Moslem population country’s not used Islamic authority as formally foundation. From this point, this paper aims to understand the concept of State moreover the Head of state from al-Mawardi> political philoshophy. With the philoshopical and Historical approached and library studies find that the concept of Indonesia State from the perspective of al-Mawardi> comes from the common aware to make community free and have a dignity. Besides that, Pancasila viewed as manifestation of Social contract and Indonesia Ideology as norms which agreed by the common peoples and also as foundation for social live and state ideology for the Indonesia. The other social contract if someone elected as leader of state, so that people must obey him as far not contradict with the Islamic values and doctrine.